Kepuasan Hidup Lansia Dalam Perspektif Pembelajaran Seumur Hidup: Tingkat dan Jenis Belajar Nonformal dan Informal di Kota Jayapura - Howay, Lusye; Sari, Inda Puspita; Angelika, Venthy; Angriyani, Dwi (JUKEJ : Jurnal Kesehatan Jompa, 2026)
AbstractBackground: Learning is a fundamental human right that extends throughout the lifespan. Therefore, the development of lifelong learning systems is essential to facilitate continuous learning opportunities for individuals at all stages of life. One population group that particularly requires such educational support is older adults, as they are expected to play an increasingly important role in social development due to rising life expectancy. Objective: This study aimed to examine the relationship between types of learning activities and life satisfaction among older adults in the city of Jayapura. Methods: The study employed a quantitative approach using Structural Equation Modeling (SEM) to analyze the relationships between variables. Results: The findings indicated that both non-formal learning (β = 0.28; p < 0.01) and informal learning (β = 0.22; p < 0.05) had a positive and significant effect on life satisfaction. The structural model produced an R² value of 0.41, indicating that 41% of the variance in life satisfaction among older adults was explained by these two types of learning activities. The goodness-of-fit indices also demonstrated that the proposed model showed an acceptable fit, indicating that the model was appropriate for explaining the observed relationships.